Appraising Research Data for Long‐Term Preservation: An Analysis of Research Data Collection Policies. Issue 1 (13th October 2021) - Kim, Jeonghyun; Faulkner, James
Abstract: Traditionally, research data has been managed independently by individual researchers and only shared at the discretion of the researcher upon request. Appraisal and selection of research data has become a major issue in recent years as the number of data types and volume of data have grown greatly, but little empirical study has been done regarding how academic libraries document their research data appraisal practices. This study surveyed academic libraries' research data collection policies, which govern the identification, appraisal, and selection of research data. A total of 17 academic libraries' research data collection policies were examined in this study.